2021
DOI: 10.3390/nano11040907
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Layer Deposition of Ni-Co-O Thin-Film Electrodes for Solid-State LIBs and the Influence of Chemical Composition on Overcapacity

Abstract: Nanostructured metal oxides (MOs) demonstrate good electrochemical properties and are regarded as promising anode materials for high-performance lithium-ion batteries (LIBs). The capacity of nickel-cobalt oxides-based materials is among the highest for binary transition metals oxide (TMOs). In the present paper, we report the investigation of Ni-Co-O (NCO) thin films obtained by atomic layer deposition (ALD) using nickel and cobalt metallocenes in a combination with oxygen plasma. The formation of NCO films wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…The CV curves of a series of SS_LiTaO-1/2 samples (Figure 4) and coatings of the Ta-O system have a general trend: in the anodic region (3.0-0.1 V), there is current amplification, which is most likely associated with the formation of SEI film [16], and no current increases are observed in the potential cathode range (4.3-3.0 V -inset in Figure 4). Further cycling at currents from 20 to 80 µA/cm2 in the cathode potential range (4.3-3.0 V) showed the presence of a minimum capacity of about 2.0-1.5 μA•h•μm-1•cm-2 (0.14-0.07 μA•h), for example in our previous work on the lithium-nickel-silicon oxide cathode study [1], the capacity of the cathode material was 30-20 μA•h•μm-1•cm-2, so we can consider that this thin film of LiTaO-1/2 does not affect on the final capacity.…”
Section: Figure 4 Cyclic Voltammetry (Cv) Curves and Results Of Cycli...mentioning
confidence: 99%
“…The CV curves of a series of SS_LiTaO-1/2 samples (Figure 4) and coatings of the Ta-O system have a general trend: in the anodic region (3.0-0.1 V), there is current amplification, which is most likely associated with the formation of SEI film [16], and no current increases are observed in the potential cathode range (4.3-3.0 V -inset in Figure 4). Further cycling at currents from 20 to 80 µA/cm2 in the cathode potential range (4.3-3.0 V) showed the presence of a minimum capacity of about 2.0-1.5 μA•h•μm-1•cm-2 (0.14-0.07 μA•h), for example in our previous work on the lithium-nickel-silicon oxide cathode study [1], the capacity of the cathode material was 30-20 μA•h•μm-1•cm-2, so we can consider that this thin film of LiTaO-1/2 does not affect on the final capacity.…”
Section: Figure 4 Cyclic Voltammetry (Cv) Curves and Results Of Cycli...mentioning
confidence: 99%
“…In the works [43,44,83], the characteristic of the crystalline phase was not detected on the XRD patterns. In one of the considered works [133], a study of coatings using electron diffraction (SAED) revealed that its structure is polycrystalline.…”
Section: The Presence Of a Crystalline Structure And The Density Of G...mentioning
confidence: 96%
“…• the cathode capacity decreases less during cycling [7,29,30,32,34,35,43,45 there is no effect of lithium-rich cathode materials on voltage reduction during cyclic charge-discharge [30,66]; • the growth of resistance during cycling is reduced [7,33,42,53,56,107,111,119,121-123, 136,153].…”
Section: Summary List Of Observed Effects On the Electrochemical Prop...mentioning
confidence: 99%
“…A single cycle consisted of NiCp2/purge/O3/purge = 1.0/10.0/6.0/10.0 s. The deposition temperature remained at 250 °C, with a sublimation temperature of NiCp2 at 110 °C. A similar growth approach was employed in previous studies [39,40]. The initial NiO film thickness for enhancing CNT growth ranged from 3.5 to 3.9 nm [41].…”
Section: Growing Of Cntsmentioning
confidence: 99%
“…NiO was deposited through the sequential exposure of CNTs to NiCp 2 and O 3 -H 2 O, with pulse durations of 1 s and 6 s, respectively, and a 10 s N 2 gas purge time. A single cycle consisted of NiCp 2 /purge/O 3 /purge = 1.0/10.0/6.0/10.0 s. The deposition temperature remained at 250 • C, with a sublimation temperature of NiCp 2 at 110 • C. A similar growth approach was employed in previous studies [39,40]. The initial NiO film thickness for enhancing CNT growth ranged from 3.5 to 3.9 nm [41].…”
Section: Growing Of Cntsmentioning
confidence: 99%